Green Synthesis of Silver Nanoparticles using Lemongrass Leaf (Cymbopogon citratus) Extract as a Reductant for Novel Colorimetric Mercury(II) Detection - Yussi Pratiwi; Yogi Febrian; Listya Eka Anggraini; Harfi Amania Khansa; Riskia Chandra Widianti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Mercury(II) contamination in water poses serious risks to human health, requiring rapid detection. This study develops a fast colorimetric sensor based on silver nanoparticles (AgNPs) synthesized using lemongrass (Cymbopogon citratus) leaf extract as a green reducing agent. Synthesis conditions were optimized, the AgNPs were characterized, and analytical performance was validated using standard parameters. Sensor responses were monitored by UV Vis spectroscopy through changes in the surface plasmon resonance (SPR) band and quantified from absorbance variations. The optimum synthesis produced a reddish brown AgNP colloid at 45 minutes, 3 mM AgNO3, and 10% lemongrass extract. The nanoparticles showed a maximum absorption at 432 nm and an average size of 150.8 nm. Validation results indicate excellent selectivity for Hg2+ and a pronounced change in the overall SPR signal at 600 ppm Hg2+. The method was linear over 0 to 0.8 ppm Hg2+ with R2 = 0.9988 (y = 0.04x + 0.0722). The limits of detection and quantification were 3.681 × 10^-9 ppm and 1.115 × 10^-8 ppm, respectively. Molar absorptivity reached 10.84 × 10^3 L mol^-1 cm^-1 at 416 nm. These results demonstrate that lemongrass mediated AgNPs provide a simple, rapid, and sensitive platform for mercury detection in water.